Ergonomic perspective : driving awkward body posture cause health problem among older taxi driver's in Malaysia - Md Yusoff, Irwan Syah; Abdul Majid, Ahmad Zuhairi; Mohd Tamrin, Shamsul Bahri (School of Social Sciences, Universiti Sains Malaysia, 2017)
World Health Organization (WHO) describe people who age above 60 years old falls into a category of older. Therefore, a 0lder community may continue to serve their services to others jobs after pension or looking light works accordance to their ability or do as a part-time job to support family economic financial and to sustain life in the challenging world. The alternative profession could involve with this community is to be taxi driver. Therefore, numerous factors should take part to ensure the older taxi drivers could serve their best performance and in good health condition. This paper aimed to drive awkward body posture cause health problem among older taxi drivers in Malaysia. A cross-sectional study was conducted with older taxi drivers using a self-administered questionnaire. It included questions on socio-demographic data, work characteristics and discomfort older taxi drivers seating posture relative to body parts (Likert scale). Purposive method sampling used base on inclusive criteria; age 60 years old and above, self-driving taxi more than 1 years, no disabilities and register with Land Public Transport Commission (LPTC). SPSS software version 2.0 used to analyze data. Total of 120 respondents participated in the study. Most of older taxi driver used hired car (76.7%) type of taxi and work as a permanent job (93.3%). More than half (53.7%) work as self-employed and smoking (55.0%). More than half respondents (76.7%) having feeling back pain past 12 months and 67.5% feeling back pain last seven days. The lower body parts potentially having musculoskeletal disorders (MSD’s) symptom and low back pain (LBP) injuries. Inappropriate seating posture among older taxi drivers may cause to discomfort and developing to MSD’s. The low awareness on ergonomics education could reflect quality lifestyle and health among older taxi drivers in Malaysia.